Delivering Positive Message Through #BaliAman Vlog: President Joko Widodo’s Communication Strategy - Anwar Anwar; Tatum Derin; Ratih Saltri Yudar; Nunung Susilo Putri; Ichsan Jazzawi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Since the seventh and current president of Indonesia, Joko Widodo (Jokowi), launched his personal video blog (vlog) channel, there has been a relatively sharp increase of studies on the President’s use of communication strategies on his vlogs. One video in particular, hashtagged with #BaliAman, was quite unique in the fact that it was meant to reduce Indonesian citizens’ fear of the state of the island after the Mount Agung’s eruption on November 2017. This present study covered the gap of the #BaliAman vlog being never studied in terms of how President Jokowi communicated the idea that Bali was safe in the face of the public’s vehement belief of the opposite. Using Penelope Brown & Stephen Levinson’s politeness theory, this present study reviewed the #BaliAman vlog to see the president’s use of the communication strategy. The results indicated that President Jokowi employed three strategies: positive face, negative face, and face threatening acts. Aside from how politeness theory applies to all situations that occur in our daily lives, this present study is significant for leaders who need to communicate safety ideas during a crisis.